Problematic aspects of the employment of convicts - Shnarbayev, B.K.; Skiba, A.P. (Bulletin of the Karaganda University “Law Series”, 2021)
The issues of providing convicts with labor are relevant not only for the penitentiary system of Kazakhstan, but also for all CIS countries, where the issues of employment for convicts arise from general problems of the economy. The relevance of the implementation of programs aimed at implementing the employment of convicts in the penal system of Kazakhstan is considered. The general problems of employment of convicts and the reasons that led to the situation in this area of the penal system are reflected. The ways of resolving the current situation based on the use of the possibilities of public-private partnership and training of specialists for the penal system in new specialties have been determined. The penal correctional system faces the challenge to provide all convicts with work, and this task is achieved in different ways. Here it is possible to use foreign experience on improving the operation of the system for organizing the work and study of convicts, in adjusting the normative legal acts governing these legal relations. One of the directions in the field of job creation in institutions can be the assistance of the government. The most effective help in the penal correctional system would be the placement of state orders at enterprises. This path is the most difficult and requires changes in a number of laws. A prototype of a state order could be the transfer of a group of goods consumed by state structures to the category of strategic importance and produce them in the correctional system